Sarcopenia: Molecular regulatory network for loss of muscle mass and function - Wu, Jiaxiang; Ding, Ping’an; Wu, Haotian; Yang, Peigang; Guo, Honghai; Tian, Yuan; Meng, Lingjiao; Zhao, Qun (Frontiers in Nutrition, 2023)
Skeletal muscle is the foundation of human function and plays a key role in producing exercise, bone protection, and energy metabolism. Sarcopenia is a systemic disease, which is characterized by degenerative changes in skeletal muscle mass, strength, and function. Therefore, sarcopenia often causes weakness, prolonged hospitalization, falls and other adverse consequences that reduce the quality of life, and even lead to death. In recent years, sarcopenia has become the focus of in-depth research. Researchers have suggested some molecular mechanisms for sarcopenia according to different muscle physiology. These mechanisms cover neuromuscular junction lesion, imbalance of protein synthesis and breakdown, satellite cells dysfunction, etc. We summarize the latest research progress on the molecular mechanism of sarcopenia in this review in order to provide new ideas for future researchers to find valuable therapeutic targets and develop relevant prevention strategies.